What do we know about the mineral resource rent sharing in Africa? - Bertrand Laporte; Céline de Quatrebarbes (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
Governments that lack the capacity to mine resources themselves have to attract foreign direct investment. However, since resources are not renewable, countries need to capture a 'fair' share of mineral resource rent to promote their development. While the sharp rise of the world prices of most minerals multiplied the total natural resources rents by 2.3 between 2002 and 2008 (World Bank data), tax revenue earned by African governments from the non-renewable natural resource sector only grew by a factor of 1.57 (Mansour, 2014). The sharing of mineral resource rent between governments and investors is often criticised for being unfavourable to African governments. But what do we really know about the sharing of mineral resource rent in Africa? The aim of this study is to review theoretical and empirical studies on rent sharing in Africa and to note their limitations regarding knowledge of the actual sharing of mineral rent.
Keywords: H25; L71; L72; L78; 330